Investigating the role of iASPP in skin homeostasis and tumourigenesis - Chung, HKK (2014)
The epidermis of skin is an essential barrier that protects the body from external stresses and retains internal body fluids. The fine balance between cell proliferation, differentiation and apoptosis as well as a well-coordinated immune response is vital in maintaining a healthy skin barrier. The iASPP protein is inhibitor of p53-mediated apoptosis and can potentially function as a proto-oncogene in tumourigenesis. Recent research has also demonstrated the regulatory role of iASPP on the transcriptional activity of p63 in mediating proper epidermal stratification. Furthermore, early data has suggested that iASPP could inhibit the DNA binding activity of the NF-kB transcription factor p65 which is critical in controlling inflammatory gene expression. The aim of this project was to investigate the autonomous role of epidermal iASPP in epidermal development and homeostasis using an in vivo transgenic mouse model system. Moreover, the role of epidermal iASPP in chemically induced skin carcinogenesis, and the possible interaction between iASPP and p65 in keratinocytes were examined.